Nonpharmacological management on reducing rheumatoid arthritis pain in the elderly: studies in social rehabilitation services unit of elderly in Garut West Java - Saida, Neng Husna; Setiawan, S; Shalahuddin, Iwan (Universitas Aisyah Pringsewu, 2019)
The elderly often undergo pain, the nature and level of pain varies from mild to severe. Handling or non-pharmacological treatment at this time is quite varied, ranging from simple methods such as distraction and relaxation to warm compresses. This research aims to determine the picture of non-pharmacological treatment in reducing the pain of rheumatoid arthritis in the elderly. The method used is descriptive quantitative. Samples were obtained with a total sampling of 30 respondents used as a research sample to determine the description of nonpharmacological treatment in reducing atheistic rheumatoid pain in the elderly. The results of this research illustrate that the elderly who experience arthritis rheumatoid pain are mild pain levels as much as 2 respondents (6.7%), moderate pain 16 respondents (53.3%), severe pain as many as 12 respondents (40.0%). The most non-pharmacological treatment efforts are doing Distraction, Masasse, Physical activity, and compressing as many as 18 people (60.0%). Conclusion of nonpharmacological treatment to reduce the pain of rheumatoid arthritis in the elderly is by way of distraction, relaxation, physical activity, masasse and compresses. The caretaker is expected to pay more attention to the handling that will be used to reduce pain.Abstrak: Lansia sering mengalami nyeri, sifat dan tingkat rasa nyeri bervariasi mulai dari yang ringan hingga yang berat. Penanganan atau pengobatan non farmakologis saat ini cukup bervariasi, mulai dari cara yang sederhana seperti distraksi dan relaksasi hingga melakukan kompres hangat. Penelitian ini bertujuan untuk untuk mengetahui gambaran penanganan nonfarmakologi dalam mengurangi nyeri atrithis rheumatoid pada lansia. Metoda yang digunakan deskriptif kuantitatif. sampel di dapatkan dengan total sampling sebanyak 30 responden dijadikan sampel penelitian untuk mengetahui gambaran penanganan nonfarmakologi dalam mengurangi nyeri atrithis rheumatoid pada lansia Hasil penelitian ini menggambarkan bahwa lansia yang mengalami nyeri atrithis rheumatoid derajat nyeri ringan sebanyak 2 responden (6.7%), nyeri sedang 16 responden (53.3%), nyeri berat sebanyak 12 responden (40.0%). Upaya penanganan non farmakologi sebagian besar adalah melakukan Distraksi, Masasse, Aktivitas fisik, dan kompres sebanyak 18 orang (60.0%). Kesimpulan penanganan nonfarmakologi untuk mengurangi nyeri atrithis rheumatoid pada lansia adalah dengan cara distraksi, relaksasi, aktifitas fisik, masasse dan kompres. Pengurus panti diharapkan dapat lebih memperhatikan mengenai penanganan yang akan digunakan untuk mengurangi nyeri.